2022
DOI: 10.3389/fpsyt.2022.834398
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Among Parents of Adolescents With Type 1 Diabetes: Associated With Fewer Parental Depressive Symptoms and Better Pediatric Glycemic Control

Abstract: BackgroundAlthough pediatric resilience plays a significant role in resisting negative moods and improving glycaemic control, little research exists regarding resilience among the parents of adolescents with Type 1 diabetes.ObjectiveTo investigate parental resilience's correlations with parental depressive symptoms, parental diabetes distress, and pediatric glycaemic control.MethodsThis cross-sectional study recruited adolescents with Type 1 diabetes and their parents from two hospitals. The parents completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…In different situations or when being exposed to risk factors, resilience helps patients solve their problems and cope better [ 46 ]. Resilience theory highlights that stressful conditions can decrease an individual’s Resilience, which may, in turn, jeopardize his/her physical and mental health [ 47 ]. This can be further suggestive that the negative impact of diabetes distress should be taken into consideration before designing interventions to increase resilience in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In different situations or when being exposed to risk factors, resilience helps patients solve their problems and cope better [ 46 ]. Resilience theory highlights that stressful conditions can decrease an individual’s Resilience, which may, in turn, jeopardize his/her physical and mental health [ 47 ]. This can be further suggestive that the negative impact of diabetes distress should be taken into consideration before designing interventions to increase resilience in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions should be aimed at fostering social support, improving diabetes management, and decreasing perceived stress, alleviating parents’ anxiety and focusing on increasing their self-efficacy. Streisand and colleagues [ 26 ] and Luo and colleagues [ 14 ] proposed that healthcare providers and educators should help to manage parental anxiety and depression, increasing their self-efficacy, and that where depression may exist, the person should be referred to a mental health specialist.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies have shown evidence of parents’ efforts to avoid hypoglycemia drives to opposite results, leading to poorer glycemic control. This must draw attention to the urgent need to educate parents in order to reduce their anxiety [ 14 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have examined the impact of resilience and stress on the lives of parents with children suffering from T1DM. The results of the first survey showed that parents who had high resilience faced fewer depressive symptoms and their children had better glycemic control [ 7 ]. Additionally, the results of the second study showed that parents who reported higher resilience had a better quality of life and better mental health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%